Cigarette Smoking Is Associated With Lower Chance of Hepatitis B Surface Antigen Seroclearance and Altered Host Immunity - Kwok, Tsz‐Yan; Hui, Rex Wan‐Hin; Mao, XianHua; Ling, Guang‐Sheng; Wong, Danny Ka‐Ho; Huang, Fung‐Yu; Fung, James; Seto, Wai‐Kay; Yuen, Man‐Fung; Mak, Lung‐Yi (Journal of viral hepatitis, 2024)
ABSTRACT Cigarette smoking is associated with worse clinical outcomes in patients with chronic hepatitis B (CHB) infection, but the effects on hepatitis B surface antigen (HBsAg) seroclearance are unclear. This study aimed to investigate the effect of active smoking on HBsAg seroclearance (SC) and its impact on peripheral blood lymphocytes in patients with CHB infection. Longitudinal follow‐up data was retrieved in 7833 antiviral‐treated CHB subjects identified from a centralised electronic patient record database (Part 1). Phenotypic analysis of peripheral blood mononuclear cells (PBMCs) from 27 CHB‐infected patients (6 active smokers; 13 with SC) was performed by flow cytometry to assess programmed death‐1 (PD‐1) expression and proportion of regulatory T cells (CD4+CD25+CD127lo). Effector function of HBV‐specific T cells was examined by comparing granzyme B (GZMB) and transforming growth factor beta (TGFβ) production in undepleted PBMCs and Treg‐depleted PBMCs after 7 days in vitro stimulation with HBV envelope protein overlapping peptides (Part 2). Over a median follow‐up of 5 years, smoking was associated with lower probability of SC (aHR 0.70, 95% CI 0.57–0.87). PD‐1 expression was increased in CD4+ T cells, CD8+ T cells and CD20+ B cells among smokers compared to non‐smokers and positively correlated with pack years (all p < 0.05). Treg depletion led to partial functional recovery of HBV‐specific T cells, with significantly bigger magnitude in smokers (p = 0.0451, mean difference = 4.68%) than non‐smokers (p = 0.012, mean difference = 4.2%). Cigarette smoking is associated with lower chance of HBsAg seroclearance, higher PD‐1 expression on lymphocytes, and impairment of effector functions of HBV‐specific T cells in CHB.